Influence of mTOR-inhibitors and mycophenolic acid on human cholangiocellular carcinoma and cancer associated fibroblasts. Issue 1 (December 2016) - Heits, Nils; Heinze, Tillmann; Bernsmeier, Alexander; Kerber, Jannik; Hauser, Charlotte; Becker, Thomas; Kalthoff, Holger; Egberts, Jan-Hendrik; Braun, Felix
Abstract Background The incidence of Cholangiocellular Carcinoma (CCA) is increasing in the western world. The tumour has a high proportion of desmoplastic stroma and is correlated with a worse prognosis when cancer associated myofibroblasts (CAFs) are present. Recent studies showed promising results after liver transplantation (LTx) in non-resectable early stage CCA. Mycophenolic acid (MPA) and the mTor inhibitor Everolimus are used to prevent organ rejection but recently were shown to exhibit an antiproliferative effect on CCA-cells. Little is known about the influence of immunosuppressive drugs on tumour cell proliferation and migration after paracrine stimulation by CAFs. Moreover, it is still unknown, which signaling pathways are activated following these specific cell-cell interactions. Methods CCA cell lines HuCCT1 and TFK1 were utilized for the study. CAFs were derived from resected CCA cancer tissue. Cell viability was measured by the crystal violet assay and tumour cell invasion was quantified using a modified co-culture transmigration assay. Semiquantitative cytokine-expression was measured using a cytokine-array. Protein expression and phosphorylation of ERK, STAT3 and AKT was determined by Western-blot analysis. Results CCA cells treated with MPA exhibited a dose related decrease in cell viability in contrast to Cyclosporine A (CSA) treatment which had no effect on cell viability. Everolimus significantly inhibited proliferation at very low concentrations. The pro-invasive effect of CAFs in co-culture transmigration assay was significantly reduced by Everolimus at a concentration of 1nM (p  = 0.047). In contrast, MPA and CSA showed no effect on tumour cell invasion. Treatment of CAFs with 1nM Everolimus showed a significant reduction in the expression of IL 8, IL 13, MCP1, MIF and Serpin E1. CCA-cells showed significant increases in phosphorylation of ERK, STAT3 and AKT under the influence of conditioned CAF-media. This effect was suppressed by Everolimus. Conclusions The secretion of proinflammatory cytokines by CAFs may lead to increased activation of JAK/STAT3-, ERK- and AKT-signaling and increased migration of CCA-cells. Everolimus abrogates this effect and inhibits proliferation of CCA-cells even at low concentrations. LTx for non-resectable early stage CCA is currently performed in several clinical studies. Consistent with a role for common immunosuppressants in inhibiting tumour cell-proliferation and -invasion, our study indicates that a combination of standard therapies with Everolimus and MPA is a promising therapy option to treat CCA following LTx.